Pelatihan dan Sosialisasi Perhitungan PPH 21 Terbaru Dengan Tarif Efektif Rata-Rata Peraturan Pemerintah Nomor 58 Tahun 2024 Tentang Tarif Pemotongan PPH Pasal 21 Pribadi Pada UMKM Lingkungan Magetan - La Ode Abdullah; Dian Kusumaningrum; Sundaru Guntur Wibowo (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
On January 1 2024, the government has changed the regulation og tax income, calculation scheme using Average Effective Rate (TER) through Government Regulation Number 58 of 2023 concerning Withholding Rates for PPh Article 21 on Income in Connection with Work, Services or Activities of Individual Taxpayers. This change in the PPh 21 deduction scheme is because the current calculation scheme can confuse taxpayers and tends to burden those who want to carry out their tax obligations properly. This challenge is also faced by MSME actors in Jonggrang Magetan Village. Seeing the diverse levels of business and promising MSMEs, MSME actors are also faced with difficulties in fulfilling their tax obligations, coupled with the new policy issued by the government regarding calculating PPH 21 using the calculation method. Therefore, in order to support MSMEs to understand and implement their tax obligations correctly, a systematic and structured training program is needed. Therefore, this proposal proposes holding Training and Socialization of the Latest PPh 21 Calculation with Average Effective Rates (TER) Government Regulation Number 58 of 2023 concerning Rates of Withholding of PPh Article 21 on Income in Connection with Work, Services or Activities of Individual Taxpayers in Magetan Environmental MSME Association.